Desain Model Pembelajaran Simulasi Untuk Menanamkan Nilai-Nilai Islami Di SMPT Manahijul Huda Tasikmalaya - Sinta setia (Prodi Pendidikan Sendratasik FKIP UMTAS, 2021)
The learning process of dance is now avoided by some schools, because the learning objectives are not comprehensively understood by all parties. But there are some schools in Tasikmalaya that teach dance in their learning process even by applying Islamic values. Islamic values ??are an important value implanted in the learners to form a good character. By analyzing two schools conducting dance lessons to apply Islamic values, researchers designed a simulated learning model for simulation development conducted at other schools in Tasikmalaya District. The Islamic values ??applied are derived from the characteristics of Prophet Muhammad SAW, namely sidiq, tabligh, amanah and fatonah. Researchers used the story stimulus of heroes of Islam to turn the story's ideas into motion while the idea of ??motion developed the motion of Ibing Pencak. Theories used in this research that is koneksionis theory, theory of adolescent development, education theory and others. This research uses Design Based Research method with qualitative approach. This research is done gradually with cycle repetition. There are 4 cycles with 6 meetings to get the design of the appropriate learning model. Based on the process that has been done got a design of learning model which is a combination of learning component in two schools, but gave new thing in the form of psychomotor aspect which is raised to apply Islamic values. Once implemented, there are changes in the behavior of learners in their daily life and the increased aspects of cognitive, affective and psychomot learners in the subject matter.